Acupoint stimulation and Chinese herbal medicines for the treatment of premature ovarian insufficiency: A systematic review and meta-analysis. (November 2020) - Li, Yuling; Xia, Guicheng; Tan, Yong; Shuai, Jiaqi
Abstract: Background and purpose: Acupoint stimulation and Chinese herbal medicines (CHM) are widely used in the treatment of premature ovarian insufficiency (POI), but the efficacy and safety remain controversial. This systematic review aims to evaluate the efficacy and safety of acupoint stimulation and CHM for POI. Methods: Seven databases were searched and collected studies comparing acupoint stimulation and CHM with hormone replacement therapy (HRT) from inception to July 31, 2019. The methodological quality of the included trials was assessed in line with the criteria of the Cochrane risk of bias assessment tool. Results: Meta-analysis was performed in 14 trials, which contained a total of 1030 women with POI. The acupoint stimulation and CHM presented advantages in normalizing of menstrual cycle (RR 2.06, 95% CI 1.62 to 2.61, P  < 0.00001) and improving perimenopausal symptoms (RR 2.00, 95% CI 1.56 to 2.56, P  < 0.00001) when compared with HRT. After treatment, compared with HRT, acupoint stimulation and CHM effectively decreased the level of follicle stimulating hormone (MD -2.88, 95% CI -5.00 to −0.76, P  = 0.008) and increased the level of estradiol (SMD 0.88, 95% CI 0.06 to 1.71, P  = 0.04). By contrast, there were no significant between-group differences in the level of luteinizing hormone (MD -3.24, 95% CI -6.77 to 0.29, P  = 0.07) and adverse effects (RR 0.31, 95% CI 0.04 to 2.54, P  = 0.28). Conclusion: This meta-analysis suggested that acupoint stimulation and CHM can serve as complementary therapies to alleviate menstrual disorders, perimenopausal symptoms, and serum sex hormone levels in POI females. Highlights: This is the first meta-analysis to evaluate the efficacy of acupoint stimulation and Chinese herbal medicines (CHM) for premature ovarian insufficiency (POI). Acupoint stimulation and CHM alleviate menstrual disorders and perimenopausal symptoms of patients with POI. Acupoint stimulation and CHM decreased the level of follicle stimulating hormone and increased the level of estradiol in POI females. Acupoint stimulation and CHM are safe and effective alternative therapies for POI.